MODEL STRATEGI BAURAN PEMASARAN DALAM MENINGKATKAN KREATIFITAS UKM BORDIR TIRAI SALINGKUANG - Andria Ningsih; Eka Hendrayani; Delfi Hurnis; Mike Triani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
SMEs are still unable to increase creativity in producing a product and also have difficulty marketing their products. have not been able to make pamphlets as a promotional tool in social media. This is an obstacle experienced by SMEs Embroidery Curtain Salingkuang. The marketing mix strategy model is a tactical marketing tool that is combined by a company or entrepreneur to produce the desired response in the target market and pursue sales targets. The method used in providing counseling and community service training is to achieve the following objectives: pretest, lecture, direct practice, media counseling, and posttest. Based on the results and discussion, it can be concluded that this service activity provides positive results. This activity can help participants or business actors. Understand that there is a marketing mix strategy model in marketing their products so that the creativity of the participants in this embroidery business can increase in producing products that have good quality and quality according to consumer demand. thereby increasing the sales of their products.